Peran Brand Image dalam Memediasi Pengaruh Green Marketing terhadap Keputusan Pembelian - Engla Desnim Silvia; Zainal A Haris; Hane Johan; Dwi Kiki Enjela (CV. ITTC INDONESIA, 2025)
The aim of this research is to examine the role of brand image on the influence of green marketing on purchasing decisions. This research was conducted on housewives in the Lubuk Begalung area of ​​Padang City who had purchased skincare products. Primary data will be collected for each respondent through a questionnaire given a score of 1-5 points. This research used a quantitative approach and involved 110 respondents offline through convenience sampling to take sample. Research data analysis used the SEM equation model with SmartPLS 3.0 software. Measurements and assessments have good relevance and predictive power. The results of the study that green marketing has a significant positive effect on brand image, green marketing has a significant positive effect on purchasing decisions, brand image has a significant positive effect on purchasing decisions, then brand image mediates the influence of green marketing and has a significant positive effect on purchasing decisions.